Calculation method of time-variant additional damping ratio and bi-objective design of RC frame with BRBs. (October 2021) - Wu, Shan; He, Haoxiang; Chen, Yifei; Chen, Jianwei
Abstract: Additional damping ratio (ADR), which plays a significant role in damped structure design, is broadly utilized to evaluate damping effect of the dampers. In current method, the ratio of energy dissipated by the dampers in one complete cycle to maximum strain energy of the structural system is adopted as the value of ADR. In the computation of damper energy dissipation, the bilinear model is commonly used to characterize hysteresis behavior of displacement-dependent dampers such as BRB. However, the accuracy of the bilinear model is not precise enough. In the light of the Bouc-Wen model can accurately characterize hysteresis behavior of various dampers, the analytical solution of hysteresis energy is derived. The ADR calculation methods based on the strain energy and the energy dissipated by the inherent damping of the main structure are proposed, respectively. The bi-objective design method of the RC frame with BRBs is put forward. The damping effect of the dampers is included in the design objectives, which makes up the deficiency of single objectives with the story drift ratio. The design objectives are that the story drift ratio of the frame does not exceed the limit, and the damping ratio reaches the expected value. The layout and force of the dampers are taken as design variables. Based on the finite element method, a RC frame with BRBs is designed iteratively. The reasonable time period length of time-varying energy is determined. Meanwhile, the strain energy method and modal damping energy dissipation method are compared and analyzed. As a result, the calculation result of strain energy method is larger than that of modal damping energy dissipation method. The strain energy method is hazardous to structural safety, and the modal damping energy dissipation method is suggested. The bi-objective design method is effective, which can further improve the structural performance.